The Impact of Tourism on the Economic Level of Business Operators in the Weluan Beach Area, Saumlaki City - Tasijawa, Lenci; Manakane, Susan Evelin; Leuwol, Ferdinand Salomo (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2023)
This study discusses the impact of tourism on the economic level of business actors in the Weluan Beach area, Saumlaki City. One beautiful panorama in Olilit Village is white sand and stretches of palm trees waving along the coastline. Weluan Beach is estimated to have a length of approximately 2 Km with a shoreline width of roughly 40 meters. Land transportation is needed in the form of two-wheeled and four-wheeled vehicles, with the distance from Saumlaki Olilit 10-15 meters, Departing from Weluan Beach, a tourist destination with beautiful panoramas. Weluan Beach tourism also has several impacts, including positive impacts as well as negative impacts. Weluan Beach also has a vital role in improving the economy of business actors, where they can sell and collect tickets. This research was conducted from 12 August to 18 September 2022 using the SWOT analysis.